Adubação da cultura da soja com fertilizante orgânico produzido a partir de carcaças de frango - Melo, Willian Silva (2020)
Organic fertilizers are a viable option to supply phosphorus (P) to the soil and improve soybean production in Paraná, especially in regions with high concentration of poultry industry where it is possible to use carcasses in addition to manure. Thus, the objective of this study was to evaluate soybean production and the availability of nutrients in the soil using doses of organic fertilizer formed from chicken carcasses compared to the use of mineral fertilizer. The work was carried out in the Yolanda district, located in the municipality of Ubiratã, western Paraná. The evaluated treatments consisted of five doses of fertilizer produced from chicken carcasses, calculated to provide 0, 30, 60, 90, 120 kg ha-1 of P2O5, that is, 0; 3.37; 6.71; 10.11 and 13.48 t ha-1, respectively. An additional treatment was also evaluated in which 60 kg ha-1 of P2O5 were applied, through 400 kg ha-1 of the mineral fertilizer NPK 10- 15-15. After harvest, the components of soybean plant production were evaluated in addition to the P content in the soil. The data were submitted to analysis of variance (ANOVA). The effect of doses of organic compost was evaluated using regression analysis, and the additional treatment was compared using contrast analysis. The use of doses of organic compound based on chicken carcass in soybean cultivation resulted in a linear increase in plant height, number of pods per plant, thousand-grain mass, grain yield and oil content in the grains. It was also efficient in increasing the P content in the soil. In comparison with mineral fertilizer, the use of organic compost resulted in a higher amount of P available in the soil, but less grain yield.